Massive freshwater transport: A new dimension for integrated water-wastewater management in North Cyprus - Gokcekus, Huseyin; Iravanian, Anoosheh; Turker, Umut; Oguz, Gozde; Sozen, Seval; Orhon, Derin (Desalination Publ, 2018)
Freshwater transport of 75 x 10(6) m(3)/y from Turkey was a milestone to solve the never-ending water problems in North Cyprus. This water transport not only covered the demand of different sectors, but it also enabled to define and implement sustainable integrated water management (IWM) strategy considering wastewater as an integral part of the management approach. The paper identified all essential components of the IWM plan, defined sustainable action strategies based on beneficial use concept. Municipal water demand, agricultural use, groundwater recharge and water-contact recreation were defined as primary beneficial uses for priority consideration. Innovative membrane bioreactor technologies were suggested for recovery and reuse of the effluents. It was recommended that (i) all urban wastewater treatment plants be upgraded/built as nutrient removal MBRs, for using the effluent directly for agriculture and/or groundwater recharge; (ii) all rural wastewaters be treated in lower-technology delivering effluents suitable for agricultural use. Energy potential of sewage was also underlined, proposing utilization of sewage sludge for energy recovery. Novel alternatives with high energy capture rates, such as high ratepyrolysis, gasification, were suggested instead of the traditional anaerobic sludge digestion. Current status of major factors and modules likely to take part in the management strategy were also covered.
Keywords: Transboundary water transport; Water management; Beneficial uses; Wastewater reuse; Groundwater recharge; Energy recovery from sludge